Microbiological observations in the anoxic basin Golfo Dulce, Costa Rica - Kuever, Jan (1996)
Our basic microbiological studies of the water column and the sediment of Golfo Dulce, Costa Rica, were focused on aerobic and denitrifying sulfur-oxidizing bacteria and anaerobic sulfate-reducing bacteria. We observed no increasing numbers of total bacterial counts within the water column. Although no oxygen was present hydrogen sulfide was only detectable close to the sediment. The highest numbers of solfate-reducing bacteria measured by Most-Probable-Number counts were found in or close to the sediment. In the anoxic bottom water sulfide-oxidizing bacteria typically containing large sulfur globules were observed microscopically. They were identified as free-swimming Thiovulum and Thiospira species. At one station large vacuolated forms of the filamentous colourless sulfur bacterium Beggiatoa were noted. Together with these sulfur containing bacteria there were long free swimming rods showing no sulfur inclusions of unknown character. The microscopic observations showed good correlation with Most-Probable-Number-counts and molecular biological techniques for sulfate-reducing bacteria.